The factors influencing consumer buying behaviour on branded goods / Suhailah Musrul - Musrul, Suhailah (2015)
Purpose - To define study of factors influencing consumer buying behaviour on branded goods that are cultural factors, social factors, psychological factors, personal factors, and situational factors. Problem statement - Consumer buying behaviour always change from time to time and each consumer have different buying behaviour towards purchasing branded goods Objective - To determine the level of buying behaviour, to identify the significant relationship between cultural factors, social factors, psychological factors, personal factors, and situational factors with buying behaviour, as well as to determine the most factor which influence buying behaviour. Methodology - A close-ended questionnaire survey is conducted with a sample size of 100 respondents. SPSS version 22.0 is used to find the data reliability, frequencies of data, descriptive analysis, correlation test, and regression test in order to test all the hypothesis involved and to also answer all the objectives that present. Summary of the findings - All independent variables are cultural factors, social factors, psychological factors, personal factors, and situational factors are significantly related to buying behaviour. Besides that, the highest level of buying behaviour is psychological factors. On the other hand, the most influencing factor affecting consumer buying behaviour on branded goods is personal factors.